THE NELSON MANDELA RULES: THE REVISED UNITED NATIONS STANDARD MINIMUM RULES FOR THE TREATMENT OF PRISONERS – SHORT REVIEW - Gruevska Drakulevski, Aleksandra (Iustinianus Primus Law Review, 2017)
The author of the paper provides a brief review of the structure of the new `Nelson Mandela Rules` - The Revised United Nations Standard Minimum Rules for the Treatment of Prisoners with the emphasizes of the most important revisions and amendments of the previous United Nations Standard Minimum Rules for the Treatment of Prisoners from 1955.The Standard Minimum Rules for the Treatment of Prisoners were adopted in 1955, and constitute since then the universally acknowledged minimum standards for the management of prison facilities and the treatment of prisoners. The Rules were revised in nine substantive areas to reflect standards that have emerged in correctional science and human rights since 1955, which are now called the Nelson Mandela Rules. This designation was made to honor the legacy of the late President of South Africa, Nelson Rolihlahla Mandela, who spent 27 years in prison in the course of his struggle for global human rights, equality, democracy and the promotion of a culture of peace.These rules represent an updated blueprint for prison management in the 21st century which upholds and promotes prisoners' dignity.
Keywords: prison, right of prisoners, Nelson Mandela, standard minimal rules, treatment, United Nations